100 YEARS OF VITAMIN D: Combined hormonal contraceptives and vitamin D metabolism in adolescent girls. Issue 3 (31st March 2022) - Öberg, Johanna; Jorde, Rolf; Figenschau, Yngve; Thorsby, Per Medbøe; Dahl, Sandra Rinne; Winther, Anne; Grimnes, Guri
Abstract : Objective: Combined hormonal contraceptive (CHC) use has been associated with higher total 25-hydroxyvitamin D (25(OH)D) levels. Here, we investigate the relation between CHC use and vitamin D metabolism to elucidate its clinical interpretation. Methods: The cross-sectional Fit Futures 1 included 1038 adolescents. Here, a subgroup of 182 girls with available 25(OH)D, 1, 25-dihydroxyvitamin D (1, 25(OH)2 D), 24, 25-dihydroxyvitamin D (24, 25(OH)2 D), vitamin D-binding protein (DBP) and measured free 25(OH)D levels, in addition to parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23), was investigated. Vitamin D metabolites were compared between girls using (CHC+) and not using CHC (CHC−). Further, the predictability of CHC on 25(OH)D levels was assessed in a multiple regression model including lifestyle factors. The ratios 1, 25(OH)2 D/25(OH)D and 24, 25(OH)2 D/25(OH)D (vitamin D metabolite ratio (VMR)) in relation to 25(OH)D were presented in scatterplots. Results: CHC+ ( n   = 64; 35% of the girls) had higher 25(OH)D levels (mean ± s.d., 60.3 ± 22.2) nmol/L) than CHC- ( n   = 118; 41.8 ± 19.3 nmol/L), P  -values <0.01. The differences in 25(OH)D levels between CHC+ and CHC− were attenuated but remained significant after the adjustment of lifestyle factors. CHC+ also had higher levels of 1, 25(OH)2 D, 24, 25(OH)2 D, DBP and calcium than CHC−, whereas 1, 25(OH)2 D/25(OH)D, PTH, FGF23 and albumin were significantly lower. Free 25(OH)D and VMR did not statistically differ, and both ratios appeared similar in relation to 25(OH)D, irrespective of CHC status. Conclusion: This confirms a clinical impact of CHC on vitamin D levels in adolescents. Our observations are likely due to an increased DBP-concentration, whereas the free 25(OH)D appears unaltered.